The Enforcement of Sanctions on Incarcerated Minors for Disciplinary Infractions (Case Study at the Class II Special Child Development Institution in Lombok Tengah) - I Putu Gede Arimbawa; I Nyoman Suarna; Wihelmus Jemarut; I Gusti Ayu Aditi; I Gusti Agung Andriani; Dwi Ratna Kamala Sari Lukman (International Forum of Researchers and Lecturers, 2024)
Children who have committed legal violations are inmates at the Class II Special Child Development Institution in Lombok Tengah. During the child rehabilitation process at LPKA Lombok Tengah, some children continue to violate the rules, making the conditions unfavorable. The purpose of this research is to ensure the legal basis for the imposition of sanctions and the enforcement of disciplinary sanctions, as well as the obstacles faced by LPKA Lombok Tengah. The method used in this writing is normative-empirical with a case, legislative, and sociological approach. The results of this study are as follows: First, the legal basis for imposing disciplinary punishment is outlined in the Decree of the Minister of Law and Human Rights Number M.HH-03.OT.02.02 of 2014 concerning guidelines for the treatment of children in LPKA. Second, the light disciplinary sanctions include verbal reprimands, moderate sanctions such as apologies and agreements between the staff and the inmates, and heavy disciplinary sanctions such as cleaning the bathroom and restricting visitation activities. The obstacles encountered include the factor of the inmates being difficult to discipline, the condition of the inmates being unwell when sanctions are to be imposed, and the factor of facilities and infrastructure.